Improved Isolation of Mesenchymal Stem Cells Based on Interactions between N-Acetylglucosamine-Bearing Polymers and Cell-Surface Vimentin - Hirohiko Ise; Kumiko Matsunaga; Marie Shinohara; Yasuyuki Sakai (Stem Cells International)
Mesenchymal stem cells (MSCs) in bone marrow and adipose tissues are expected to be effective tools for regenerative medicine to treat various diseases. To obtain MSCs that possess both high differentiation and tissue regenerative potential, it is necessary to establish an isolation system that does not require long-term culture. It has previously been reported that the cytoskeletal protein vimentin, expressed on the surfaces of multiple cell types, possesses N-acetylglucosamine- (GlcNAc-) binding activity. Therefore, we tried to exploit this interaction to efficiently isolate MSCs from rat bone marrow cells using GlcNAc-bearing polymer-coated dishes. Cells isolated by this method were identified as MSCs because they were CD34-, CD45-, and CD11b/c-negative and CD90-, CD29-, CD44-, CD54-, CD73-, and CD105-positive. Osteoblast, adipocyte, and chondrocyte differentiation was observed in these cells. In total, yields of rat MSCs were threefold to fourfold higher using GlcNAc-bearing polymer-coated dishes than yields using conventional tissue-culture dishes. Interestingly, MSCs isolated with GlcNAc-bearing polymer-coated dishes strongly expressed CD106, whereas those isolated with conventional tissue-culture dishes had low CD106 expression. Moreover, senescence-associated β-galactosidase activity in MSCs from GlcNAc-bearing polymer-coated dishes was lower than that in MSCs from tissue-culture dishes. These results establish an improved isolation method for high-quality MSCs.